2009
DOI: 10.1007/s00415-009-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral subthalamic nucleus stimulation in advanced Parkinson’s disease: Five year follow-up

Abstract: Our data confirm that bilateral STN stimulation is beneficial in the long-term for PD patients but does not prevent disease progression and the occurence of axial levodopa unresponsive signs in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 56 publications
10
117
1
2
Order By: Relevance
“…Since the introduction of STN DBS in 1993, many clinical studies have shown that this therapy is safe and effective [2,3] during a 4- to 8-year follow-up [4,5,6,7,8,9]. However, from studies with a longer follow-up we learned that the motor benefit slowly wears off because of disease progression with axial and non-motor symptoms, which do respond sufficiently to dopaminergic medication and stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of STN DBS in 1993, many clinical studies have shown that this therapy is safe and effective [2,3] during a 4- to 8-year follow-up [4,5,6,7,8,9]. However, from studies with a longer follow-up we learned that the motor benefit slowly wears off because of disease progression with axial and non-motor symptoms, which do respond sufficiently to dopaminergic medication and stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…10,28,29,33,35,65 However, a large multicenter study 91 found that the completed suicide rate following subthalamic DBS in PD is less than 0.5%, suggesting that suicide occurrences are unlikely to influence data significantly in this regard. We found that there are no long-term studies comparing the several therapeutic strategies for PD that adequately report objective data concerning anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen observational studies fulfilled the selection criteria. Two of these studies were excluded 16,17 because the population samples were subsets of the populations in 2 other articles that were included because they had larger sample sizes. 18,19 Of the remaining 11 studies, 3 examined bilateral GPi, 9 examined bilateral STN stimulation, and 1 study included both STN and GPi target sites.…”
mentioning
confidence: 99%